<span>B. 2d^2+6d-7. Should be the correct answer.</span>
Answer:
3x(2x - 3)
Step-by-step explanation:
Given
y = 6x² - 9x ← factor out 3x from each term
= 3x(2x - 3)
Answer: -3
X = -3
Step-by-step explanation:
Multiply the numbers i hope this helps god bless
Step-by-step explanation:
Hi mate I am new to this app
Answer:
t = 13
Step-by-step explanation:
3 months ------ 4500
6 months ------ x
3/6 = 4500/x
cross multiplation:
3x =27000
x = 9000,or we should have just doubled the wages, since the time doubled
3 months ------ 4500
5 months ------ y
3/5 = 4500/y
3y = 22500
y = 7500
3 months ------- 4500
t months -------- 19500
3/t = 4500/19500 = 3/13
3t = 39
t = 13